Survey Pembinaan Atlet Tenis Junior Buluran Tenis Club Jambi (Btc) - Aini, Jumratul; Ali, Muhammad; Iqroni, David (Dharmas Journal of Sport, 2025)
The purpose of this study was to observe the coaching of tennis athletes at the Buluran Tennis Club in Jambi City. The benefits of this study are expected to see how the coaching of tennis athletes at the Buluran Tennis Club in Jambi City and tennis in general. This study was conducted at the Buluran Tennis Club in Jambi City, located at Jl. Mayjen Sutoyo No. 1 Telanaipura, Jambi City, adjacent to the Telanaipura Police Station in Jambi City, near the FKIK Campus of Jambi University. After the data was obtained, the data was analyzed quantitatively using a percentage formula. The results of the study showed that the coaching process at the Buluran Tennis Club (BTC) in Jambi City was running well and was structured, with routine evaluations that received positive responses from 100% of respondents. As many as 91.7% of respondents assessed that the mental and discipline aspects of athletes had been considered, although they still needed improvement. The training program was designed according to the needs of the athletes and received full support from all respondents. However, only 50% of respondents stated that physical training was carried out routinely. In addition, although the facilities and infrastructure are available, 91.7% of respondents felt that their maintenance was not optimal. Overall, BTC needs to improve physical training, mental coaching, and facility maintenance to support more effective and sustainable athlete coaching. Therefore, although coaching at BTC Jambi has been running well, improvements in the aspects of individualized training, periodic evaluation, and completeness of supporting facilities need to be made so that coaching can take place optimally and sustainably.